Комары подрода Aedes (Diptera, Culicidae) фауны СССР. II. Aedes dahuricus sp. n - Данилов, В.Н. (Вестник зоологии, 1987)
Aeaes (Aedes) dahuricus sp. n. is described (female, male genitalia, 4th instar larva). Type-locality: Kubukhai, Onon Region, Chita District. The species is distributed over the South of East Siberia, Far East USSR, Japan; it is suggested to occur in Mongolia, NE China and Korea.